Higher Neutrophil-lymphocyte Ratio in TB/HIV Co-infection Compared to Pulmonary Tuberculosis - Nuni Sulastri; Bachti Alisjahbana; Resvi Livia; Edhyana Sahiratmadja (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: Neutrophils and lymphocytes play a significant role in inflammation and a high ratio of neutrophils over lymphocytes (NLR) has been used as an inflammatory marker to predict the severity of various diseases. Here we compared the NLR among pulmonary tuberculosis and TB/HIV co-infection.METHODS: A retrospective cross-sectional study was conducted, included patients with pulmonary TB without cavitation TB (n=50), with cavitation TB (n=50) and HIV co-infection (n=27). Complete blood count was examined, including neutrophils and lymphocyte. NLR was calculated and compared between groups. RESULTS: Neutrophils were significantly higher (p=0.004) in TB with cavitation compared to those with no cavitation (8.27±1.45 x103/μL vs. 6.61±1.4 x103/μL, respectively); whereas the lymphocytes were similar in both groups, resulting in a significantly higher NLR (p=0.009) in pulmonary TB with cavitation compared to pulmonary TB with no cavitation (5.98±1.85 vs. 4.42±1.86, respectively). On the contrary, both neutrophils as well as lymphocyte were significantly lower in TB/HIV compared to pulmonary TB, which for neutrophil were 5.14±2.19 x103/μL vs. 7.4±1.45 x103/μL, respectively (p=0.003) and for lymphocyte (1.02 ±0.57 x103/μL vs. 1.57±0.64 x103/μL, respectively (p=0.001), resulting in a significantly higher (p=0.041) NLR value in TB/HIV (6.05±2.67) compared to pulmonary TB (5.16±1.88).CONCLUSION: High NLR in pulmonary TB with cavitation as well as in TB with HIV co-infection may be of great interest for biomarker in TB severity. Further study confirming NLR as potential marker is imperative.KEYWORDS: lymphocyte, neutrophil, NLR, tuberculosis, TB/HIV